Variation in body mass index and their determinants among married women in Uttar Pradesh - Maheshwari, Sonam; Singh, Brijesh; Singh, Omprakash; Gupta, Puneet (International Journal of Health, 2015)
The body mass index of married women is a high quality sign of a countryâ€™s health status as well as economic condition. NutritionÂ Â Â research in India has previously focused on the serious problem of under nutrition related to nutrient deficit and high rates of infection. BMI provide an indicator for supporting to wipe out many preventable diseases. Alteration in nutritional status plays an important role in the course of a personâ€™s health. Hence, BMI can be used as an indicator for nutrition status, and association with some diseases can be expected. This study observes the emerging nutrition transition among 7559 married and currently non â€“pregnant women aged between 15-49 years and also the differential impact of some demographic, socioeconomic, environmental and health-related factors on the body mass index living in Uttar Pradesh, India. The third wave of National Family Health Survey (2005-06) data provides nationally representative data on womenâ€™s weight and height. Average BMI is 21.11 kg/m2, and a turn down tendency in BMI was found during the last about 20 years.Â Body mass index increased with increasing age, education level of the woman, standard of living index. Lower BMI was especially pronounced among women who were living in rural areas, Hindus, employed women and women who are anemic.